Perbedaan Pengaruh Orang Tua, Teman dan Iklan Terhadap Anak dalam Pemilihan Produk Mainan Berdasarkan Pada Jenis Kelamin dan Tempat Tinggal Anak - Arif Muanas (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2021)
This study analyzes the differences in the influence of parents, friends, and advertisements on children in choosing toy products based on the gender and residence of the children. The gender review is based on the premise that boys and girls have very basic differences or traits in choosing-decisions. Based on residence, it is based on the consideration that the availability of various facilities, complete information and facilities as well as a more modern social environment in the city causes children who live in the city to tend to be more brave and open in deciding a product choice. The method used is t test using independent sample test which is possible to analyze the significance level of differences in the influence of parents, friends and advertisements on children in choosing toy products. Data were obtained from 200 boys and girls aged 9-12 years and living in cities and villages. The results of this analysis indicate that the effect of advertising on boys and girls has a significant difference. In addition, the influence of parents on children living in cities and children living in villages also has a significant difference.